Curriculum of Hatred and intolerances in Pakistan: A glimpse into Khyber Pakhtunkhwa textbooksCur - Khan, Rizwan; Ullah, Ihsan; Abdul Wahab, (Pakistan Review of Social Sciences (PRSS), 2021)
This is Qualitative study conducted in Swat, a District of Khyber Pakhtunkhwa, situated in Northwestern Pakistan. The target population of this study was Educationist, Intellectuals, secondary school teachers, University and College Lecturers, Members of KP curriculum board and Lawyers. The aim of this study was to know the nexus between hatred, intolerance and design curriculum of KP. For such purpose a total 30 in-depth interviews were conducted with expert in such field to examine the dilemma critically that how the course curriculum and textbooks influence the young minds. All these interviews were semi-structured, and the respondents were selected randomly. It was found that there is a strong nexus between hatred, intolerance and the design curriculum of KP. The analytical and critical investigation of the study not only disclose the connection between violence, hatred and course curriculum but also project some valuable recommendations which will eventually drag the attention of policy makers toward this context.